Identification and evaluation of quercetin as a potential inhibitor of naphthoate synthase from Enterococcus faecalis. Issue 11 (28th July 2019) - Das, Satyajeet; Batra, Sagar; Gupta, Pramodkumar P.; Kumar, Mukesh; Srivastava, Vijay Kumar; Jyoti, Anupam; Singh, Nagendra; Kaushik, Sanket
Abstract: Enterococcus faecalis is a gram‐positive, rod‐shape bacteria responsible for around 65% to 80% of all enterococcal nosocomial infections. It is multidrug resistant (MDR) bacterium resistant to most of the first‐line antibiotics. Due to the emergence of MDR strains, there is an urgent need to find novel targets to develop new antibacterial drugs against E .  faecalis . In this regard, we have identified naphthoate synthase (1, 4‐dihydroxy‐2‐naphthoyl‐CoA synthase, EC: 4.1.3.36; DHNS) as an anti‐ E . faecalis target, as it is an essential enzyme for menaquinone (vitamin K2 ) synthetic pathway in the bacterium. Thus, inhibiting naphtholate synthase may consequently inhibit the bacteria's growth. In this regard, we report here cloning, expression, purification, and preliminary structural studies of naphthoate synthase along with in silico modeling, molecular dynamic simulation of the model and docking studies of naphthoate synthase with quercetin, a plant alkaloid. Biochemical studies have indicated quercetin, a plant flavonoid as the potential lead compound to inhibit catalytic activity of Ef DHNS. Quercetin binding has also been validated by spectrofluorimetric studies in order to confirm the bindings of the ligand compound with Ef DHNS at ultralow concentrations. Reported studies may provide a base for structure‐based drug development of antimicrobial compounds against E .  faecalis . Abstract : This study gives the preliminary structural details of Naphthaote synthase from Enterococcus faecalis. This study also presents the in silico model and interaction studies of Quercetin with the protein. Further, it proposes Quercetin as a potential lead molecule against Naphthaote synthase.